Ben Jonson : vol. 10 - Jonson, Ben; Jonson, Ben; Herford C. J.; Simpson, Evelyn (Oxford : Clarendon press, 1950)
Poster for Federal Theatre Project presentation of "Volpone" at the Mayan Theatre, showing a skull with gold coins.
Keywords: English Drama -- California -- 1930-1950.; Theatrical posters -- 1930-1950.; Screen prints -- Color -- 1930-1950.